Using CR1aa versus KSOM as the culture medium for in vitro embryo production of cattle - Endang Triwulanningsih; M.R Toelihere; J.J Rutledge; T.L Yusuf; B Purwantara; K Diwyanto (Indonesian Center for Animal Research and Development (ICARD), 2002)
This research has been conducted at the laboratory of in vitro fertilization in the Department of Animal Science University of Wisconsin, USA. These embryos can be used for improving genetic value of Indonesian cattle. Oocytes were matured in TCM- 199 medium (in 5% CO2 incubator and at 390C) enriched with follicle stimulating hormone (FSH) 10 μl/ml, oestradiol 17 β 1μl/ml and 10% Fetal Calf Serum (FCS). The oocytes were fertilized in vitro with motile sperm and incubation between sperm and oocytes in fertilization medium Tyroide Albumin Lactate Pyruvate (TALP) for 20 hours. All zygotes were cultured in CR1aa (n=1549) medium versus modification of protein-free pottasium simplex optimized medium (KSOM) (n=675) up to blastocyst stage and were fed FCS 5 μl/50 μl medium on day 6, as treatment A and B respectively. Data were analyzed by completely randomized design with SAS program. Percentages of cleavage, morula, blastocyst, expanded blastocyst, unfertilized and degenerated ova in this study were 91.4% vs 75.6 %; 75.6% vs 58.9%; 61.5% vs 38.5%; 31.2% vs 5.1%, 8.6% vs 24.4%, 15.7% vs 8% which were significantly different (P<0.01) for treatment CR1aa and KSOM respectively. Based on this study, CR1aa medium is better culture medium than KSOM for efficient in vitro production (IVP) of bovine embryos. Key words: Oocytes, in vitro fertilization, embryo, blastocyst, culture medium